MATERI PEMBELAJARAN PENCEMARAN LINGKUNGAN: ANALISIS KRITIS ATAS PENELITIAN TERBARU - Akbar, Khoironi Fanana; Riris Idiawati; Hilya Wildana Sofia; Ulfiyatul Fitriyah (JEAS (Journal of Educational and Applied Science), 2024)
Environmental pollution has emerged as a pressing global issue necessitating urgent attention. Environmental education stands out as a pivotal approach to enhance public awareness regarding the significance of environmental conservation. Learning materials addressing environmental pollution play a crucial role within environmental education frameworks. This article aims to critically analyze recent research concerning environmental pollution learning materials. Employing a literature review methodology, this study examines recent literature pertinent to environmental pollution learning materials. The analysis reveals that effective environmental pollution learning materials should consider the social, cultural, and environmental contexts of the students. Furthermore, these materials should be presented in an engaging and interactive manner to facilitate better comprehension and retention among students. This research provides recommendations for the development of more effective and relevant environmental pollution learning materials tailored to the needs of students. It is anticipated that this study will make a positive contribution to the advancement of environmental education and efforts towards fostering a better environment.